Rota dos murais da UFSM: uma proposta de roteiro turístico na perspectiva do turismo cidadão - Fialho, Aline Britto (2022)
Heritage education is a permanent and systematic process of educational work which, combined with a set of other actions, such as tourist management strategies, turns out to be a powerful instrument for cultural valorization and dissemination, facilitating the understanding of the sociocultural universe we are in. The main objective of the product “UFSM Murals Route” is to propose a cultural itinerary with UFSM’s extensive collection of mural art as the central theme. Employing theoretical references, interviews, collection and analysis of data, the study was developed with the purpose of identifying the heritage’s potential as a cultural attraction and, therefore, to contribute to its visibility and valorization through the resignification of these spaces, using heritage interpretation in order to bring the community closer to the institution's memory. The tourist experience has the ability to stimulate and facilitate the valorization of cultural resources by local communities, giving visitors the opportunity to develop and transform the way they interpret them, resulting in a different perception of their daily lives.